OBJECTIVE EVALUATION OF CONSUMER STEREOSCOPIC 3D DISPLAY TECHNOLOGIES USING ELECTROENCEPHALOGRAPHIC (EEG) SIGNALS - RAJA KHAIRUDDIN, RAJA NUR HAMIZAH (2014)
The growing public acceptance towards three-dimensional (3D) technology has definitely made 3D become more and more popular especially in the entertainment industries worldwide. Though substantial progress has been made in studying the impact of3D contents from the ergonomics perspective, research regarding brain and stereovision is still limited. Thus, this research has two main purposes: (i) to investigate which consumer 3D stereoscopic technologies (i.e., active shutter and passive polarized systems) is better for 3D content viewing and (ii) to verify whether 3D does provide better visualization of the scene than 2D. For this study, forty subjects were selected among university students, aged between 19 to 25 years old who had experienced in watching 3D movies in the past and had no visual and cognitive impairments. Electroencephalogram (EEG) and electrocardiogram (ECG) data were recorded while subjects randomly viewed a series of movie clips in three different visual modes, 2D, 3D active and 3D passive.